Examining the economic impact of floods in selected Indian states. (15th March 2020) - Panwar, Vikrant; Sen, Subir
ABSTRACT: This study is an attempt to shift the focus of research pertaining to the relationship between natural disasters and economic growth from national to sub-national level. Using augmented panel vector auto-regression models (PVAR-X), this study examines the sector-specific economic impact and growth dynamics following floods in 24 selected Indian states over the period 1990–2015. Results indicate that floods have negative growth effects in the short-term across economic sectors except for the agricultural sector, where the effects were observed to be positive. Contrary to the existing literature, the positive effects of floods on the agricultural sector were not found to be spilling over to other economic sectors. Severe floods, unlike moderate ones, have either negative or statistically non-significant growth effects which persisted in the long-term as well. Overall, the study found floods to have diverse impacts across economic sectors, the extent of which is influenced by the state-wise levels of human development and underlying intensities of the flooding events. This study may stimulate the policy makers to direct their efforts towards taking effective and sustainable preventive measures before the flood occurs and ensure prompt response, recovery and reconstruction during and after the flood so as to build India's overall disaster resilience.